A Personal Introduction to Knud Illeris’ Problemorientering og Deltagerstyring: Oplæg til en Alternativ Didaktik - Anders Melbye Boelt (Journal of Problem Based Learning in Higher Education)
This paper presents a personal introduction to Knud Illeris’ Problemorientering og deltagerstyring – oplæg til en alternativ didaktik [Problem-orientation and participant-direction – a draft for an alternative didactic], published first in 1974. Illeris is one of the founding fathers of PBL in Denmark, and 50 years after its first publication it seems fitting to re-read the book, and I hope others will do the same. Introduced to PBL as something sprawling from the counterculture, youth rebellion, and progressive pedagogies, I found Illeris’ book to be both inspiring and a bit underwhelming, and in many cases foreshadowing neoliberal conceptions of outcome-based education.